Effect of Hyflex Learning on Student's Academic Performance in Education Technology in Kwara State - Danyaro, Abdu; Attah, Justina Ojoma; Sallah, Bolanle Hafsat (International Journal of Universal Education, 2024)
The study examined the effect of Hyflex learning on Student's Academic Performance in Education Technology in Kwara State. The study was guided by two research questions and two null hypotheses were postulated for the study. The study adopted a quasi-experimental research design of 2 x 2 factorial design. The target population were all 400-level undergraduate students in the Department of Educational Technology offering EDT 412. A sample size of 152 undergraduate students participated in the study. Two groups were involved in the study which are both intact classes. The experimental group where full-time undergraduates’ students while the control group were sandwich undergraduates’ students. The instrument used for data collection was an educational technology performance test which was validated by three educational technology experts. Descriptive statistics of mean and standard deviation were used to answer the research questions while inferential statistics of t-test were used to analyse the research hypothesis. The findings of the study revealed that Hyflex learning effectively improved the performance of undergraduate students in education technology. Both male and female undergraduate students in the experimental group performed better than their counterparts in the control group, though the male students had a higher mean score than their female counterparts. There is a significant difference between the mean post-test score of students taught educational technology using Hyflex learning relative to their counterparts taught using the lecture method and there is a significant interaction effect of gender on the mean scores of students in the experimental group. It was therefore recommended among others that institutions should adopt hyflex learning as a pedagogy because it offers flexible learning opportunities among undergraduate students.